Developing Global Perspectives Through Study Abroad Programs For Edu Global Senior High School Students: Implementation, Impact, And Community Engagement - Min Adlina; Moh. Aria Badar (Faatuatua Media Karya, 2025)
This community service program aims to empower high school students with global perspectives through a short term overseas study initiative. Conducted under the educational mission of Edu Global School Medan, the program involved Indonesian students studying in Australia. Using Pierre Bourdieu’s framework (habitus, capital, and field), the activity measured the impact of international exposure on students’ personal development, intercultural competencies, and social engagement. The results show significant transformations in students’ confidence, communication, and adaptability. Furthermore, the program contributes to the educational community by offering a replicable model of global learning integration at the secondary education level